PELAKSANAAN KEDAULATAN NEGARA ATAS PENGELOLAAN SUMBER DAYA ALAM MELALUI MEKANISME PERSYARATAN PERDAGANGAN - I Wayan Titib Sulaksana; A Indah Camelia (Universitas Airlangga, 2012)
The trade between countries is the main important key to increase people’s prosperity. It is mainly because the prosperity can be measure with nation’s balance of trade. However, the trade has to be adjusted to the national resources and has to think of nation’s souvereignty. In everyt trade between countries, there will be a condition in which souvereinty will be interefered by one of the member of the trade—for example in forms of pure trade or exploitation nation resources. Therefore, the requirements of trade between two members of trade are needed in order that it won’t interfere by nation’s souvereignty and also won’t exploit all of nation resourcesKeywords: Souvereignty, Trade, Nation resources